APARTHEID AND COLLECTIVE TRAUMA PERFORMATIVITY IN “AMNESTY” BY NADINE GORDIMER - Wahyu Gandi G; Achmad Munjid (International Conference on Social and Islamic Studies, 2021)
This study aims to reveal the impact and response to the apartheid system in shaping the collective trauma of African society through symbolic representations of suffering and social performativity through political action in “Amnesty” short story’s Nadine Gordimer. This study used the cultural trauma theory by Jeffrey Alexander with descriptive qualitative method. The results of this research show that social suffering is symbolically represented with a humanist and theocentric images. Even so, the two seemingly different treatments are essentially the same suffering, disguised by social and cultural symbols. Then, as a response to this suffering, there was social performativy through the political actions of social agents carried out by the Labor Union. These actions occur after going through of socio-cultural processes such as gathering, organizing, rioting, speeches, demonstrations, and accommodating or representing pain as well as distributing social awareness to arrive at the point where the apartheid system is the cause of all forms of suffering they experience.